Editorial for the Special Issue “MEMS Packaging Technologies and 3D Integration” - Seonho Seok (Micromachines, 2022)
As fabrication technologies advance, the packaging of MEMS device is being developed in two main directions: MEMS device packaging and MEMS or sensor system integration [...]